Learning Styles and Preferred Teaching Methodologies of Medical Students In Relation To Year of Study - Muhammad Zafar Iqbal Hydrie; Syed Muhammad Zulfiqar Hyder Naqvi; Syed Imtiaz Ahmed Jafry (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
Objective: To assess learning styles and preferred teaching methodologies of medical students in relation to year of study. Methods: A cross-sectional study was carried out among 523 medical students of Baqai Medical College, Baqai Medical University, Karachi, from May 2019 to October 2019. All male and female students from first to final year, who attended the undergraduate MBBS program in the medical college, were included in the study. The study questionnaire was administered to all enrolled undergraduate medical students, from first to fifth year, on the campus out of which 523 forms were collected. The study instrument was a questionnaire containing students' demographic details, David Kolb's Learning Style Inventory 4.0 and their preferred teaching methodologies scored using a 5 point Likert scale. The association of various learning styles and preferred teaching methodologies with year of study was assessed by using Pearson chi-square test. Results: Out of 523 students who returned the form 518 had completed the questionnaire. A majority of the students had imagining or experiencing learning style. No change in learning style was observed between years of study. The top three teaching methodologies with highest mean scores were small group discussion (3.58±1.12), problem based learning (3.56±1.11) and demonstration on models (3.54±1.20). A significant association between some preferred teaching methodologies and year of study was found such as interactive lecture (p=0.011), problem based learning (p=0.026), small group discussion (p=0.024), and one way lecture (p=0.028) while a highly significant association was noted in case of student presentation (p=0.001). Conclusion: The present study showed that different years of study at medical schools did not significantly affect students' learning styles, although the students did change their preferences to some teaching methodologies. Longitudinal studies are necessary to reveal whether there is an effect of learning styles over time in medical education.